PEGylated PLGA nanoparticles: unlocking advanced strategies for cancer therapy - Prashant Kesharwani; Vishal Kumar; Khang Wen Goh; Garima Gupta; Abdulrhman Alsayari; Shadma Wahab; Amirhossein Sahebkar (Molecular Cancer)
Abstract Poly(lactic-co-glycolic acid) (PLGA) is a widely utilized biodegradable and biocompatible polymer in drug delivery systems, particularly for encapsulating drug molecules with poor solubility and permeability. PLGA nanoparticles, composed of polylactic acid (PLA) and polyglycolic acid (PGA), offer tunable properties such as controlled degradation rates and drug release kinetics. The PEGylation of PLGA nanoparticles results in the formation of a polyethylene glycol (PEG) corona on their surface, which enhances systemic circulation by reducing opsonization and immune system recognition. This extended circulation time increases the likelihood of nanoparticles reaching the target site, a crucial advantage in cancer therapy, as it allows for reduced dosage frequency while improving therapeutic efficacy. Furthermore, surface functionalization with targeting ligands enables selective delivery to specific cells or organs via ligand-receptor interactions, facilitating enhanced cellular uptake and intracellular drug release. This review provides a comprehensive analysis of PEGylated PLGA nanoparticles in cancer diagnosis and therapy, highlighting recent advancements, current challenges, and future perspectives in their clinical translation. Graphical abstract